PENTINGNYA SIKAP RESPEK BAGI PENDIDIK DALAM PEMBELAJARAN - Eliasa, Eva Imania (MAJALAH ILMIAH PEMBELAJARAN, 2011)
The background of this article came from violence cases at school which encompass physical & psychological violence. Some data show these thoughtful conditions need to be treated immediately to anticipate broader (larger) consequences for teachers, students and education word in Indonesia. Teachers use some kinds of abuse behavior forms as a means to make students be discipline. However, these are not such a right way for that purpose. Therefore they will need an educational practice which is humanist for students. One of the supportive aspects for humanistic education is respect. Respect is an attitude that admits, appreciate views and stand points of students without underestimate them, open to have communication with, and not only provide academic valuation but also psychological security and give them success experiences. More ever, mutual respect is also important in learning activities because it can improve student learning interests and motivations. In sum, teachers need to have that kind of attitude (respect), so they can contribute to the attainment of learning goals maximally.